IMPLEMENTASI UJRAH TENAGA KERJA PERSPEKTIF EKONOMI ISLAM UD HSN DESA KONANG GALIS PAMEKASAN - Fahrurrozi, Fahrurrozi (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2022)
Islamic economics regulates the procedure for payment of wages given by employers to workers with the principle of humanity where between employers and workers must be mutually beneficial. UD HSN is one of the petis-making factories in Konang Village, Galis District, Pamekasan Regency. The problem that becomes the main study in this research, namely, how is the implementation of labor ujrah applied to UD HSN in Konang Village, Galis District, Pamekasan Regency in an Islamic economic perspective. This research uses a qualitative approach with descriptive qualitative research. The results of this study indicate that: the implementation of labor ujrah at UD HSN from an Islamic economic perspective has fulfilled the requirements for providing wages in an Islamic economy, namely wages must be clear and there is a mutual agreement regarding the amount of wages, the wage system, the work system, and so on. However, when talking about the principle of wages in the Islamic economy, namely fair, decent wages, and not delaying payments, it is still not fully fulfilled at UD HSN because of the driver and packaging workers, the wages received are still below the Pamekasan UMK.